Synthesis and Biological Evaluation of HDAC Inhibitors With a Novel Zinc Binding Group - He, Junquan; Wang, Songsong; Liu, Xingang; Lin, Ruili; Deng, Fang; Jia, Zhong; Zhang, Chenghong; Li, Zhao; Zhu, Hongtian; Tang, Lei; Yang, Pingrong; He, Dian; et al. (Frontiers in Chemistry, 2020)
Vorinostat (SAHA) with great therapeutic potential has been approved by the FDA for the treatment of cutaneous T-cell lymphoma as the first HDACs inhibitor, but the drawbacks associated with hydroxamic acid group (poor stability, easy metabolism, weak binding ability to class IIa isozymes, and poor selectivity) have been exposed during the continuous clinical application. Based on the pharmacophore of HDAC inhibitors, two series of compounds with novel zinc binding group (ZBG) were designed and synthesized, and the antitumor bioactivities were evaluated in four human cancer cell lines (A549, Hela, HepG2, and MCF-7). Among the synthesized compounds, compounds a6, a9, a10, b8, and b9 exhibited promising inhibitory activities against the selected tumor cell lines, especially compounds a9 and b8 on Hela's cytostatic activity (a9: IC50 = 11.15 ± 3.24 μM; b8: IC50 = 13.68 ± 1.31 μM). The enzyme inhibition assay against Hela extracts and HDAC1&6 subtypes showed that compound a9 had a certain broad-spectrum inhibitory activity, while compound b8 had selective inhibitory activity against HDAC6, which was consistent with Western blot results. In addition, the inhibitory mechanism of compounds a9 and b8 in HDAC1&6 were both compared through computational approaches, and the binding interactions between the compounds and the enzymes target were analyzed from the perspective of energy profile and conformation. In summary, the compounds with novel ZBG exhibited certain antitumor activities, providing valuable hints for the discovery of novel HDAC inhibitors.